2013
DOI: 10.1128/aac.01345-13
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Isoniazid and Rifampin Are Decreased in Adult Pulmonary Tuberculosis Patients with Diabetes Mellitus

Abstract: Plasma isoniazid and rifampin concentrations, but not pyrazinamide and ethambutol concentrations, were decreased by about 50% (P < 0.05) in diabetic pulmonary tuberculosis patients. The prevalences of subnormal plasma isoniazid, rifampin, pyrazinamide, and ethambutol concentrations were 49% or 100% (P < 0.01), 66% or 100% (P < 0.05), 30% or 50% (P ‫؍‬ 0.198), and 32% or 21% (P ‫؍‬ 0.742) in nondiabetic or diabetic tuberculosis patients, respectively. These data show that plasma concentrations of isoniazid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 18 publications
(25 reference statements)
0
69
0
1
Order By: Relevance
“…Babalik et al reported that the plasma INH concentration at 2 h postdosing was lower in patients with TB and DM than those with TB (17). These decreases are most likely due to higher body weights of TB patients with DM and, hence, the lower drug doses (in milligrams per kilogram of body weight) received by TB patients with DM than those without DM.…”
Section: Discussionmentioning
confidence: 97%
“…Babalik et al reported that the plasma INH concentration at 2 h postdosing was lower in patients with TB and DM than those with TB (17). These decreases are most likely due to higher body weights of TB patients with DM and, hence, the lower drug doses (in milligrams per kilogram of body weight) received by TB patients with DM than those without DM.…”
Section: Discussionmentioning
confidence: 97%
“…However, overweight and obesity is not routinely taken into account for drug adjustment during TB treatment. Thus, it is possible that TB-2DM patients who are overweight are receiving suboptimal doses of TB medications, and could be contributing to their reported lower plasma levels (Babalik et al, 2013;Nijland et al, 2006;Ruslami et al, 2007). In these studies, suboptimal levels of TB medications have been attributed to chronic hyperglycemia or to a possible interaction between drugs for the management of DM and TB (Baker et al, 2011;Ruslami et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for these pharmacokinetic alterations are related with the interactions between drugs for TB and T2DM, reduced absorption or defective liver function in T2DM patients. (Babalik et al, 2013;Baker et al, 2011;Nijland et al, 2006;Ruslami et al, 2010;Ruslami et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effect of DM on the plasma concentrations of first-line anti-TB drugs [61,[66][67][68][69][70]. The results, however, are conflicting; in some studies, DM was associated with decreased plasma levels of rifampicin and isoniazid [66,69,70], whereas in others, there was no clear relationship between the plasma concentrations of first-line anti-TB drugs and DM [61,67,68]. It should be noted that in some studies, only the 2-and 6-h plasma concentrations of the anti-TB drugs were measured, whereas for other studies, the intensive blood sampling or the population pharmacokinetic approach was used.…”
Section: Patients With Diabetes Mellitusmentioning
confidence: 99%